PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI METODE OVERVIEW, ASK, READ, WRITE, EVALUATE, TEST (OARWET) PADA SISWA KELAS V SD - laili, zahra (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Improving Reading Comprehension Skills Using Overview, Ask, Read, Write, Evaluate, Test (OARWET) Method for the Fifth Grade Students. The objectives of this research is to improve reading comprehension skills for the fifth grade students of SD Negeri Tanjungrejo in the academic year of 2015/2016. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of four meetings including planning, action, observation, and reflection. Subjects of the research were 15 students of the fifth grade of SD Negeri Tanjungrejo. Techniques of collecting data were observation, documentation, interview, and test. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. The results of this research showed that the application of OARWET method can improve reading comprehension skills for the fifth grade students of SD Negeri Tanjungrejo in the academic year of 2015/2016. Keywords: overview, ask, read, write, evaluate, test (OARWET) method, reading comprehension Abstrak: Peningkatan Kemampuan Membaca Pemahaman Melalui Metode Overview, Ask, Read, Write, Evaluate, Test (OARWET) pada Siswa Kelas V SD. Tujuan penelitian ini adalah untuk meningkatkan kemampuan membaca pemahaman siswa kelas V SD Negeri Tanjungrejo tahun ajaran 2015/2016. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan selama tiga siklus dengan lima kali pertemuan yang kegiatannya meliputi: perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SD Negeri Tanjungrejo yang berjumlah 15 siswa. Teknik pengumpulan data dalam penelitian ini, yaitu: observasi, dokumentasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukkan bahwa penerapan metode Overview, Ask, Read, Write, Evaluate, Test (OARWET) dapat meningkatkan kemampuan membaca pemahaman siswa kelas V SD Negeri Tanjungrejo tahun ajaran 2015/2016. Kata kunci: metode overview, ask, read, write, evaluate, test (OARWET); membaca pemahaman